The Influence of Entrepreneurship Learning and Career Guidance on Economic Education Students' Entrepreneurial Interest - Ulfa Lufiana; Ifeatu Oliobi; Bernard Yungu Loleka (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This research was conducted to determine whether or not there was an influence of entrepreneurship learning and career guidance on economic education students' interest in entrepreneurship. Methodology:This research uses quantitative research with descriptive research type. The population in this study were all Economic Education students, totaling 57 students. The data collection technique used in this research is a questionnaire to determine Entrepreneurship learning and Career Guidance in fostering interest in entrepreneurship. The data analysis technique used in this research is multiple linear regression analysis with a significance level of 0.05. Main Findings: The research results can be concluded that there is a positive and significant influence of Entrepreneurship learning and Career Guidance learning together on Economic Education students' entrepreneurial interest with a simultaneous contribution value of 43.5%. Novelty/Originality of this study: The novelty of this research is that it is an incentive for lecturers to carry out learning as interestingly as possible in order to increase understanding of entrepreneurship and foster students' interest in entrepreneurship.